Adrenomedullin reduces the severity of cerulein-induced acute pancreatitis - DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (ELSEVIER SCIENCE INC, 2007)
We investigated the effect of Adrenomedullin (AM) on cerulein-induced acute pancreatitis in rats. AM treatment (100 ng/kg per rat, subcutaneous) after one hour of cerulein injection reduced the plasma amylase levels, pancreatic weight, pancreatic malondialdehyde (MDA) levels, and the severity of the lesions microscopically. These data suggest that AM has a protective effect on cerulein-induced acute pancreatitis. These could be due to anti-inflammatory properties of AM, inhibition of proinflammatory cytokine secretion, reducing the endothelial permeability increased by reactive oxygen species, endotoxins or cytokines. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: adrenomedullin; acute pancreatitis; cerulein; BINDING PROTEIN-1; MACROPHAGE; CYTOKINES; UROCORTIN; INJURY